Undifferentiated Intimal Sarcoma of the Inferior Vena Cava with Extension to the Right Atrium and Renal Vasculature. (28th May 2015) - Afzal, Aasim M.; Alsahhar, Jamil; Podduturi, Varsha; Schussler, Jeffrey M.
Abstract : Primary sarcomas of the great vessels (aorta, pulmonary artery, and inferior vena cava (IVC)) are exceedingly rare. We report a rare case of an undifferentiated intimal sarcoma of the IVC with extension to the right atrium, adrenal, and renal veins. The patient underwent extensive resection, reconstruction of the IVC, and subsequent adjuvant chemotherapy. Patient has tolerated chemotherapy and, at 17 months after resection, the patient remains free of tumor recurrence. Undifferentiated intimal sarcomas remain a rare entity with only five cases of venous undifferentiated intimal sarcomas reported in the literature, two of which occurred in the IVC. Intimal sarcomas tend to carry a poor prognosis with the limited literature available on treatment approaches. Our objective is to highlight this rare entity and possible treatment approach which we utilized. Primary sarcomas of IVC need to be included as part of a complete differential diagnosis in patients with atrial masses or recurrent pulmonary emboli.